Detection of Extracellular Vesicles Using Proximity Ligation Assay with Flow Cytometry Readout—ExoPLA. Issue 1 (5th July 2017) - Löf, Liza; Arngården, Linda; Ebai, Tonge; Landegren, Ulf; Söderberg, Ola; Kamali‐Moghaddam, Masood
Abstract: Extracellular vesicles (EVs) are continuously released by most cells, and they carry surface markers of their cells of origin. Found in all body fluids, EVs function as conveyers of cellular information, and evidence implicates them as markers of disease. These characteristics make EVs attractive diagnostic targets. However, detection and characterization of EVs is challenging due to their small size. We've established a method, called ExoPLA, that allows individual EVs to be detected and characterized at high specificity and sensitivity. Based on the in situ proximity ligation assay (in situ PLA), proximal oligonucleotide‐conjugated antibodies bound to their targets on the surfaces of the EVs allow formation of circular products that can be fluorescently labeled by rolling circle amplification. The intense fluorescent signals produced in this assay allow detection and enumeration of individual EVs by flow cytometry. We describe the procedures for ExoPLA, along with expected results and troubleshooting. © 2017 by John Wiley & Sons, Inc.